THRESHOLD-BASED VIDEO SHOT BOUNDARY DETECTION: A COMPREHENSIVE APPROACH FOR TRANSITION IDENTIFICATION - Sharma, Sarika; Malakar, Pritendra Kumar (ShodhKosh: Journal of Visual and Performing Arts, 2024)
This paper proposes a comprehensive threshold-based algorithm for detecting video shot boundaries, identifying both abrupt and gradual transitions. The proposed method uses frame-to-frame histogram comparisons combined with a dynamic thresholding mechanism to identify significant changes between frames. Extensive experiments were conducted on various video datasets to evaluate the effectiveness of the algorithm in detecting both types of transitions. The proposed method outperforms traditional methods, offering improved accuracy in boundary detection with reduced computational complexity. The experimental results confirm that this approach is well-suited for applications in video editing, surveillance, and automated content analysis.